Continuous-time state-space modelling of the hot hand in basketball - Sina Mews; Marius Ötting (AStA Advances in Statistical Analysis, 2021)
We investigate the hot hand phenomenon using data on 110,513 free throws taken in the National Basketball Association. As free throws occur at unevenly spaced time points within a game, we consider a state-space model formulated in continuous time to investigate serial dependence in players' success probabilities. In particular, the underlying state process can be interpreted as a player's (latent) varying form and is modelled using the Ornstein-Uhlenbeck process. Our results support the existence of the hot hand, but the magnitude of the estimated effect is rather small as the underlying success probabilities are elevated by only a few percentage points.
Keywords: 510; Free throws; Hot hand; Irregularly sampled data; Ornstein-Uhlenbeck process; Sports analytics; State-space model